Diagnóstico sobre la generación de empleo de las empresas purificadoras de agua en la comuna San Jerónimo, parroquia Chongón, cantón de Guayaquil - Zambrano Cantos, Esther Isabel (2018)
This research work aims to get a diagnosis on the generation of employment of water purification companies in the commune of San Jerónimo, Chongón parish, Guayaquil. It pointed out that one of the first problems that exist in San Jerónimo community of Chongón parish is the lack of stable or formal employment, so they have been in need of employment in an informal way or work for hours on a walking basis……….